Impact of transitioning from antibiotic use to antibiotic-free practices on broiler dead-on-arrival rates: A bayesian structural time series approach - Panneepa Sivapirunthep; Pranee Pirompud; Veerasak Punyapornwithaya; Supitchaya Srisawang; Chalita Jainonthee; Chanporn Chaosap (Poultry Science, 2025)
This study assessed the impact of transitioning from an antibiotic (AB) to an antibiotic-free (ABF) production system on dead-on-arrival (%DOA) rates during broiler transport. Data from 105,898 truckloads across 200 to 280 farms over six years were analyzed, comparing three years before (2015-2017) and after (2018-2020) the ABF transition. Decomposition analysis revealed a decline in %DOA from 2015 to 2017, followed by stability until 2019 and another decline into 2020. Seasonal fluctuations were observed, with %DOA peaking between February and April and reaching its lowest point in October. Changepoint analysis identified six significant shifts in %DOA, with the highest values occurring in 2015. Following the ABF transition, %DOA temporarily increased for about six months before stabilizing. Bayesian structural time series (BSTS) analysis showed that observed %DOA closely matched predicted values, indicating no significant effect from the ABF transition (p = 0.485; posterior probability = 51 %). These findings suggest that transport mortality can be effectively controlled without antibiotics by maintaining robust practices, such as improved sanitation, controlled rearing stocking density, optimized brooding, and enhanced pre-slaughter management.
Keywords: Animal Nutrition and Physiology; Animal Behavior and Welfare Studies; Insect and Pesticide Research